2013
DOI: 10.3906/tar-1207-49
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and rheological characteristics of alcohol free probiotic boza produced using Lactobacillus casei Shirota: Estimation of apparent viscosity of boza using non-linear modeling techniques

Abstract: Variations in cutting forces were investigated experimentally depending on infeed angles and cutting areas in the external threading on a CNC turning centre. For this purpose, AISI 1050 workpiece material, 16ERM AG 60 IC 908 cutting tool, and SER 2525 M16 tool holder were used. External threading operations were performed using 0 • , 14.5 • , 15 • , 27.5 • , and 30 • infeed angles while the cutting speed was held constant at 100 m/min for the experiments. Experimental results showed that the infeed angle and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
(46 reference statements)
3
10
0
Order By: Relevance
“…As can be seen, shear stress values of the boza samples increased with an increase in shear rate, indicating that all the boza samples showed shear thinning behavior (Steffe, 1996;Rao, 1999;Sikora et al, 2007) at both temperature levels. The obtained data were described by an Ostwald-de Waele model with R 2 values higher than 0.99, which was in accordance with the previous studies (Genc et al, 2002;Zorba et al, 2003;Öztürk et al, 2013). The model parameters [namely, consistency coefficient (K) and flow behavior index (n)] of the boza samples at 5 and 20 °C are presented in Bourne, 2002) are also shown in Table 2.…”
Section: Effect Of Temperature and Applicability Of Coxmerz Rulesupporting
confidence: 72%
“…As can be seen, shear stress values of the boza samples increased with an increase in shear rate, indicating that all the boza samples showed shear thinning behavior (Steffe, 1996;Rao, 1999;Sikora et al, 2007) at both temperature levels. The obtained data were described by an Ostwald-de Waele model with R 2 values higher than 0.99, which was in accordance with the previous studies (Genc et al, 2002;Zorba et al, 2003;Öztürk et al, 2013). The model parameters [namely, consistency coefficient (K) and flow behavior index (n)] of the boza samples at 5 and 20 °C are presented in Bourne, 2002) are also shown in Table 2.…”
Section: Effect Of Temperature and Applicability Of Coxmerz Rulesupporting
confidence: 72%
“…Öztürk et al . () reported rheological properties of alcohol‐free probiotic boza samples, and these boza samples also showed pseudoplastic behavior. Fresh boza samples had a flow behavior index ranging from 0.52 to 0.62.…”
Section: Resultsmentioning
confidence: 98%
“…Using Lactobacillus casei Shirota, Öztürk et al . () produced alcohol‐free probiotic boza and determined its physicochemical, rheological and sensory characteristics during storage. Authors reported that acidity of boza samples played a significant role in perceived taste by panelists, and liking scores for alcohol‐free boza samples were negatively influenced with an increase in acidity.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the literature, there are some reports (Daglıoglu, 2000;Zorba et al, 2003;Hatzikamari et al, 2007a;Cosansu, 2009;Ozer et al, 2010;Kabak and Dobson, 2011;Altay et al, 2013;Ozturk et al, 2013) on general composition, microbiological processes, and preparation methods of traditional Turkish foods and beverages. Therefore, this review aims to characterize some traditional Turkish cereal-based fermented products in their traditional production methods, fermentation conditions and microorganisms.…”
Section: Introductionmentioning
confidence: 99%